A System for Documentation of Cleft Lip and Nose Deformity and Postoperative Analysis - Agarwal, Rajiv; Bhatnagar, S K; Chandra, Ramesh (Indian Journal of Plastic Surgery, 1995)
A reliable system of documentation of the extent of deformity of the cleft lip, alveolus, palate and nose is essential to compare treatment methods and results of this common problem. We are presenting here a symbolic system of documenting preoperative deformity, intraoperative technique and postoperative status in cleft lip nose deformity which is based on previously published diagnosis and documentation systems. Modified striped Y system is used to document the extent of the deformity and this is combined with standard measurements for the cleft lip nose deformity and charts to document the intraoperative steps. We find this to be simple and reliable for the analysis of the results.